Recombinant and In Vitro RNA Synthesis Methods and Protocols - Conn, Graeme L.; Conn, Graeme L. (Methods in Molecular Biology, 2012)
The discovery of catalytic RNAs in the mid-1980s marked the beginning of a new era in RNA biology and an ever increasing appreciation of the diverse and critical roles played by this fascinating molecule. In Recombinant and In Vitro RNA Synthesis: Methods and Protocols, expert researchers in the field detail approaches from the inception of a new RNA project to the final sample ready for analysis. These experimental protocols combine established work-horse approaches with some of the latest innovative methods for RNA synthesis and purification. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Recombinant and In Vitro RNA Synthesis: Methods and Protocols aids scientists in continuing to study the fascinating world of RNA.